الاقتصاد الأخضر وتحديات البيئة نحو التنمية المستدامة - رزيق، رحيمة Ruzaiq, Rahimah; زواقري، الطاهر Zouaqri, Altaher (جامعة الشهيد حمه لخضر الوادي, 2024)
يحرص الاقتصاد الأخضر على تحسين رفاهية الإنسان والعدالة الاجتماعية، لكن هذا لا ينبغي أن يكون على حساب إهمال العامل البيئي، ذلك أن وجود البيئة ونوعيتها تشكل عاملا هاما في رفاهية الإنسان، التي تتطلب بدورها استغلال البيئة والموارد الطبيعية ومساهمتها في تراكم الثروة للقضاء على الفقر والمرض والحرب. الاقتصاد الأخضر عمل منذ ولادته على إنهاء الأزمة البيئية كمشكلة اقتصادية، باعتباره وسيلة لتحقيق التنمية المستدامة، وليس بديلا عنها من جهة، وأساس لتحقيق التكامل بين الأبعاد الأربعة للتنمية المستدامة، وهي الأبعاد البيئية والاقتصادية والاجتماعية والتقنية أو الإدارية. وبالرغم من أن الاقتصاد الأخضر اقتصاد جديد مبتكر ومولد للدخل وفرص العمل بفضل الجيل الجديد من الوظائف والقطاعات النظيفة المؤدية إلى ابتكار استراتيجيات مختلفة لمكافحة التراجع البيئي، إلا أن هذا لم يمنع من وجود آراء تناقض مدلوله وغاياته. إن تحديات الاقتصاد الأخضر، هي تحديات اقتصادية وبيئية واجتماعية، تلعب فيها العوامل البشرية والمالية دورا رئيسيا، خاصة في ظل انبعاثات الغازات الدفينة وتغير المناخ وغيرها من المخاطر. الأمر الذي دعا رجال السياسة والاقتصاد والقانون للتدخل بهدف تطوير الاقتصاد الأخضر، وذلك من خلال زيادة الموارد المالية المخصصة لحماية البيئة، مما يسهم في تحقيق الرفاهية وطرق توزيعها بشكل عادل يحقق التنمية المستدامة. The green economy strives to improve human well-being and social justice; however, this should not come at the expense of neglecting the environmental factor, as the presence and quality of the environment are crucial factors in human well-being. In turn, human well-being requires the exploitation of the environment and natural resources, contributing to wealth accumulation to eradicate poverty, disease, and war. Since its inception, the green economy has worked to address the environmental crisis as an economic issue, considering it a means to achieve sustainable development rather than an alternative. It serves as a foundation for integrating the four dimensions of sustainable development: environmental, economic, social, and technological or administrative dimensions. Despite being an innovative and income-generating economy, creating new opportunities for employment through the new generation of clean jobs and sectors, the green economy has not been immune to conflicting opinions regarding its implications and goals. The challenges of the green economy encompass economic, environmental, and social aspects, where human and financial factors play a crucial role, especially in the context of greenhouse gas emissions, climate change, and other risks. This has prompted political, economic, and legal authorities to intervene in order to develop the green economy by increasing financial resources allocated to environmental protection. This contributes to achieving well being and its fair distribution, ultimately realizing sustainable development.
Keywords: التلوث البيئي -- الأمن الغذائي -- الأمن الإنساني -- التغيرات المناخية